Study of some physiological parameters hyssop (Hyssopus officinalis) in the vegetative stage under the influence of salinity - Omolbanin Jahantigh (Zīst/shināsī-i Giyāhī-i Īrān, 2016)
The most important abiotic stresses is salinity, the high levels of sodium which is toxic to most varieties of plants species, and more importantly affect plant growth and limit the plants yield capacity. Hyssopus officinalis L. has been known as a culinary and medicinal herb for hundreds of years, it is cultivated globally. Although Hyssopus officinalis L. is one of valuable medicinal plants and its cultivation is continuously being extended in the world, no information is available on the responses of this plant to salinity. Since the growth stages are very sensitive to stress, in this research the effects of salinity on growth parameters of Hyssopus officinalis L. in seedling stage were studied. The treatments were six levels (0, 2, 4, 6, 8 and 10 dS m-1 of saline water). The results showed that with increasing the salinity stress, protein, cartenoids, oligosaccharides and reducing sugar, MDA and H2O2 contents significantly increased however total chlorophylls, chl a and chl b contents and total sugar and polysaccharides significantly decreased. It seems that increasing the amount of protein, cartenoids and carbohydrates are important risk factors for resistance to salt Hyssopus officinalis L.